Digital controller design for microalternator set - Majid, M. S.; Jamaan, S.; Muda, Z.; Rahman, H. A.; Hassan, M. Y. (IEEE, 2000)

(untitled)
A digital controller for the microalternator set was implemented in the power laboratory, Universiti Teknologi, Malaysia. Description of the hardware and software development is presented in this paper. This paper also presents test results of an automatic voltage regulator using the PI and PID control of various loads